2020
DOI: 10.21037/atm-20-7342
|View full text |Cite
|
Sign up to set email alerts
|

T cell co-stimulator inducible co-stimulatory (ICOS) exerts potential anti-atherosclerotic roles through downregulation of vascular smooth muscle phagocytosis and proliferation

Abstract: Background: Atherosclerosis (AS) is a chronic inflammatory disease. The role of the immune system in the etiology of the disease, particularly T cells, has been widely studied and is well established. T cell activation directly regulates co-signaling molecules present in immune synapses. Targeting one or several of these cosignaling molecules can inhibit T cell-mediated inflammation and delay or reduce AS. In recent years, this strategy has increasingly become a research focus. As such, we explored the role an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It has been reported that ICOS may play an antiatherosclerotic role by inhibiting the phagocytosis and proliferation of HASMCs during the formation of atherosclerotic plaques (20). In this experiment, the relationship between ICOS and HASMCs was detected by co-cultivation of JK-ICOS cells and HASMCs.…”
Section: Hasmcs Lipid Phagocytosis Significantly Inhibited After Trea...mentioning
confidence: 83%
See 3 more Smart Citations
“…It has been reported that ICOS may play an antiatherosclerotic role by inhibiting the phagocytosis and proliferation of HASMCs during the formation of atherosclerotic plaques (20). In this experiment, the relationship between ICOS and HASMCs was detected by co-cultivation of JK-ICOS cells and HASMCs.…”
Section: Hasmcs Lipid Phagocytosis Significantly Inhibited After Trea...mentioning
confidence: 83%
“…However, this was not explicitly verified in the study, and its mechanism was not explored in depth. Our preliminary experiments have found that the expression of ICOS in the aortic atherosclerotic plaques of APOE KO rats was significantly reduced, and the overexpression of ICOS could inhibit the phagocytosis and proliferation of HASMCs (20). This experiment tested the main lipid phagocytic receptors involved and found CD36 has significant differences.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…[ 110 ] In addition, controlling the T follicular helper-germinal center B-cell axis by blocking the CD8 + Treg ICOS-ICOSL pathway could reduce the development of atherosclerosis, [ 111 ] and ICOS has an antiatherosclerotic effect by inhibiting aortic smooth muscle cell phagocytosis and proliferation to delay plaque formation in apoE −/− mouse models. [ 112 ] Furthermore, in a mouse atherosclerosis model, the expression of ICOS in the spleen was decreased, and promoting ICOS activity could provide a useful strategy for the prevention of atherosclerosis.…”
Section: B7-cd28 Family and Atherosclerosismentioning
confidence: 99%